E. coli Bacteriostatic Action Using TiO2 Photocatalytic Reactions - Thammasak Rojviroon; Sanya Sirivithayapakorn (International Journal of Photoenergy)
This experimental research comparatively investigates the Escherichia coli (E. coli) bacterial inactivation of the TiO2 photocatalytic thin films fabricated by the sol–gel dip-coating (SG) and low-temperature spray-coating (SP) techniques, with low-intensity (12 μW·cm−2) UVA-light-emitting diodes (UVA-LED) as the light source. The bacteriostatic experiments were undertaken using the nutrient broth (NB) and 0.85% NaCl with the initial E. coli concentrations of 102, 104, 106, and 108 CFU·mL−1. Moreover, the essential physical characteristics of the SG-TiO2 and SP-TiO2 photocatalytic thin films were determined prior to the experimental bacterial inactivation. The findings showed that both photocatalytic thin films possessed the ideal physical characteristics, especially the SP-TiO2 thin film. In addition, the viable cell counts, the cell morphology, and the bioluminescence-based adenosine triphosphate (ATP) indicated that both SG-TiO2 and SP-TiO2 thin films under UVA could effectively inhibit the proliferation of the E. coli cells in both NB and 0.85% NaCl.